IMPLEMENTASI MODERASI DAN INKLUSIVITAS BERAGAMA BAGI GEN-Z DI SMA BUDDHIS BODHICITTA MEDAN - Ernida Marbun; Josua Chariston Simanungkalit; Astuti Purwasari; Muhammad Irfan; Sri Novita Tondang (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
The purpose of this activity is to strengthen the values of religious moderation and inclusivity among young generations, particularly students of SMA Buddhis Bodhicitta Medan, to become tolerant, open-minded individuals who appreciate diversity in a multicultural society. This activity responds to the need for character education that not only focuses on academic aspects but also develops social attitudes and humanitarian values essential for living together peacefully and harmoniously. The methods used involve an interactive and participatory approach through group discussions, interfaith guest lectures, role-playing simulations, and guided reflection sessions. This approach provides space for students to internalize experiences and values of tolerance and respect for differences in daily life. The results showed a significant increase in students’ awareness and openness toward religious and cultural differences, reflected in their active participation and reflective responses. The program also successfully created a more inclusive school climate, built safe and constructive dialogue spaces, and encouraged collaboration among students that strengthened solidarity and mutual respect. In conclusion, this structured and reflective character education program effectively shapes a young generation that upholds the values of tolerance, inclusivity, and peace. This model has great potential to be replicated in various educational institutions as a strategic effort to strengthen interreligious harmony and maintain national unity in pluralistic Indonesia.